1994
DOI: 10.1128/aac.38.12.2817
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose pharmacokinetics of piperacillin and tazobactam in infants and children

Abstract: The pharmacokinetics of piperacillin and tazobactam were assessed after single-dose administration to 47 infants and children. Study subjects ranging in age from 2 months to 12 years were randomized to receive one of two different doses of a piperacillin-tazobactam combination (8:1): a low dose (n = 23) of 50 and 6.25 mg of piperacillin and tazobactam per kg of body weight, respectively, or a high dose (n = 24) of 100 and 12.5 mg, respectively. The pharmacokinetic behavior of tazobactam was very similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
46
6

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 32 publications
8
46
6
Order By: Relevance
“…Piperacillin-tazobactam CL was significantly associated and increased with surrogate covariates of maturation, including body weight, PMA, PNA, and SCR. This finding is consistent with prior investigations of piperacillin-tazobactam PK in infants and was expected given that the kidneys are the primary route of elimination for this drug (7,19,25). In our population, piperacillin-tazobactam CL increased rapidly (on average, by 100%) after the first 2 weeks of life.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Piperacillin-tazobactam CL was significantly associated and increased with surrogate covariates of maturation, including body weight, PMA, PNA, and SCR. This finding is consistent with prior investigations of piperacillin-tazobactam PK in infants and was expected given that the kidneys are the primary route of elimination for this drug (7,19,25). In our population, piperacillin-tazobactam CL increased rapidly (on average, by 100%) after the first 2 weeks of life.…”
Section: Discussionsupporting
confidence: 81%
“…Our slightly lower CL may reflect the lower GA at birth in our study population. Overall, differences in piperacillin-tazobactam CL across ages can be attributed to the maturation of renal function during childhood (19). Similarly, population V estimates in our study were not clinically different (within 15%) from reported V estimates for older children (19).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Piperacillin concentrations in serum were analyzed by high-performance liquid chromatography by a modification of the method of Reed et al (14). For piperacillin, briefly, 0.2 ml of a methanol solution containing 50 mg of methicillin/liter as an internal standard was added to an equal volume of serum sample, and the mixture was centrifuged.…”
Section: Methodsmentioning
confidence: 99%